Fiscal policy on Peru’s gross domestic product through fiscal multipliers, 2000 – 2022 - Jhunniors Puscan Visalot; Omer Cruz Caro; Alex Javier Sánchez Pantaleón; Einstein Sánchez Bardales; Angelica María Carrasco Rituay; River Chavez Santos (Cogent Economics & Finance)
This study examines the impact of fiscal policy on Peru’s Gross Domestic Product (GDP) using fiscal multipliers and a structured vector autoregressive (SVAR) model to analyze the economic response to fiscal shocks. Fiscal multipliers were analyzed in the context of current government spending, capital spending, and taxes, considering quarterly data, to investigate their effects on Peru’s real gross domestic product. Using an SVAR methodology and impulse response analysis (IRF), it was possible to obtain that, after an increase in current spending, GDP initially decreases; and as time passes, it fluctuates and recovers. Capital spending shows that an increase leads to an almost immediate increase in GDP, and in the long term, it maintains stability. On the other hand, in response to taxes, initial negative effects were found in the short term. However, they are offset and tend to stabilize, where the magnitude and duration of this effect depend on several economic and political factors.